2004
DOI: 10.1177/230949900401200123
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Anterior Dislocation of the Hip Associated with Ipsilateral Femoral Shaft Fracture in a Child: A Case Report

Abstract: Traumatic anterior dislocation of the hip joint in children is rare, and only one case with ipsilateral femoral fracture has been reported in Japan. We report a case of such dislocation and a review of the literature. The patient was a 31-month-old girl who was injured in a car accident while asleep on a tilted front passenger seat. Radiographic examination showed dislocation of the right obturator foramen and transverse fracture of the ipsilateral femoral shaft. The dislocation of the right hip was easily red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…74.4% was reported in Brazil [19]. A Japanese review of traumatic dislocations of the hip in children found that <5% of hip dislocations were associated with femoral fractures [42].…”
Section: Associated Injuriesmentioning
confidence: 99%
“…74.4% was reported in Brazil [19]. A Japanese review of traumatic dislocations of the hip in children found that <5% of hip dislocations were associated with femoral fractures [42].…”
Section: Associated Injuriesmentioning
confidence: 99%
“…Barquet et al [1] in a case report reviewed the literature and found 35 cases of ipsilateral hip dislocation with fractures of the shaft femur. The injury combination reported above is extremely rare, with only two similar cases being reported in the English literature to date in the paediatric age group [6,7]. In adults, injury combinations of obturator type of anterior hip dislocation with fracture neck femur [8] or intertrochanteric [9]/subtrochanteric femur fractures [10] have been reported, but not in combination with shaft femur fracture.…”
Section: Discussionmentioning
confidence: 73%
“…On impact with a four-wheeler from behind, the boy must have been compressed between the two individuals because of sudden deceleration, leading to hyperabduction of the hip, thereby causing an Reduction of the dislocated hip is the priority in the management of such cases. In a similar case reported by Yamamoto et al [7], the anterior hip dislocation reduced spontaneously while obtaining plain radiographs. Malkawi et al [6] reported a case with a similar injury profile in a 7-yearold male child, but in this case, the femur fracture was subtrochanteric in location and the anteriorly dislocated femur head also caused occlusion of the femoral artery.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations